The bone shard war - Stewart, Andrea (Andrea G.) (Stewart, Andrea (Andrea G.). Drowning empire, 2023)
"Lin Sukai has won her first victory as Emperor, but the future of the Phoenix Empire hangs in the balance--and Lin is dangerously short of allies. As her own governors plot treason, the Shardless Few renew hostilities. Worse still, Lin discovers her old nemesis Nisong has joined forces with the rogue Alanga, Ragan. Both seek her death. Yet hope lies in history. Legend tells of seven mythic swords, forged in centuries past. If Lin can find them before her enemies, she may yet be able to turn the tide"--